2001
DOI: 10.1046/j.0022-0477.2001.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal potential and early growth in 14 tropical mangroves: do early life history traits correlate with patterns of adult distribution?

Abstract: Summary 1We characterized the dispersal potential and early growth traits of 14 tropical mangrove species in experiments where diaspores were immersed in various solutions of seawater and subsequently stranded onto surfaces with the same salinity. 2 Viviparous and non-viviparous species had similar buoyancy, seed weight and rates of root and shoot initiation, as well as early growth and salinity tolerance. This trait convergence may be related to selection against small, dormant diaspores in the unstable regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 33 publications
2
137
1
1
Order By: Relevance
“…Sediment accretion and erosion evidently influences the ability of propagules to disperse and establish, which therefore influences the spatio-temporal changes in mangroves (Clarke et al, 2001;Sousa et al, 2007). Most of propagules were found to disperse over a short distance up to tens of metres (McGuinness, 1997;Breitfuss et al, 2003;Sousa et al, 2007;De Ryck et al, 2012).…”
Section: Implication For Mangrove Management and Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment accretion and erosion evidently influences the ability of propagules to disperse and establish, which therefore influences the spatio-temporal changes in mangroves (Clarke et al, 2001;Sousa et al, 2007). Most of propagules were found to disperse over a short distance up to tens of metres (McGuinness, 1997;Breitfuss et al, 2003;Sousa et al, 2007;De Ryck et al, 2012).…”
Section: Implication For Mangrove Management and Conservationmentioning
confidence: 99%
“…In addition, propagule buoyancy, period of obligate dispersal, anchoring time, tides, currents, wind and even dyke removal are primary factors determining dispersal and establishment of mangroves (Clarke, 1993;McGuinness, 1997;Di Nitto et al, 2013;Van der Stocken et al, 2013). After stranding and establishment, other factors become important in determining survival including predation, interspecific competition, flooding regime, and soil physico-chemical characteristics (Clarke et al, 2001;Delgado et al, 2001;Cannicci et al, 2008;Krauss et al, 2008). As stated by Duke et al (1998), if (an adult specimen of) a species is present, the environment must be suitable for it, but the opposite does not apply.…”
Section: Implication For Mangrove Management and Conservationmentioning
confidence: 99%
“…The high growth rates and the relative insensitivity to changes in survival and establishment of propagules and seedlings seem to indicate that mangroves' strategy of reproduction is adapted to less favourable conditions with higher losses, especially for the young growth stages. Indeed, studies have reported quite a high variability in propagule and seedling survival (Bhat et al 2004;Clarke and Kerrigan 2002;Clarke et al 2001;Hogarth 1999;Kitaya et al 2002). Given the life-history parameters in our model, reforestation should present no problem in most areas.…”
Section: Discussionmentioning
confidence: 99%
“…Buoyancy is regarded as an important factor as well as the period of obligate dispersal and anchoring time (Clarke and Myerscough 1991;Clarke 1993;Delgado et al 2001). A. marina propagules have an obligatory dispersal period of around 10 days (Clarke 1993;Clarke et al 2001;Hogarth 1999 (Clarke 1995). Mangroves may be able to reproduce around their fifth year.…”
Section: Life-history Of Mangrovesmentioning
confidence: 99%
“…The aspects of the dispersal and recruitment mechanisms in mangroves have rarely been studied. Of these, it is mainly the biotic aspects such as propagule development and abundance, propagule predation and establishment that have received attention (Rabinowitz 1978a,b, Saenger 1982, Smith 1988, Clarke 1993, McKee 1995, Clarke et al 2001. Mangroves share the common feature of buoyancy of the reproductive organ, which is an ecological response to life in the tidal environment (Chapman 1976, Tomlinson 1986).…”
Section: Introductionmentioning
confidence: 99%